THE ANALYSIS OF GREEN MARKETING AND BRAND IMAGE ON REPEAT PURCHASE ON CONSUMERS OF COFFEE SHOP IN BANDUNG - Hasanah, Yulia Nur; Aziz, Fauzan (ASEAN Marketing Journal, 2021)
Manuscript type: Research Article Research Aims: This research was conducted to examine the influence of green marketing and brand image to the repeat purchase of consumer of coffee shop in Bandung. Design/Methodology/Approach: Data were collected through online survey that targeted the consumer of coffee shop in Bandung area. A method of successive interval (MSI) and Partial Least Square (PLS) was used as a method to analyse this data Research Findings: The results shows that green marketing and brand image have a significant effect on repeat purchases simultaneously and separately. Based on these results, consumers of coffee shops in Bandung were able to explain that 65.6% of repeated purchases were influenced by green marketing and brand image while the remaining 34.4% was influenced by other factors. Theoretical Contribution/Originality: By understanding that the green marketing and brand image can influencing the repeat purchase of consumer of coffee shop in Bandung, one can compare future studies especially in the field of marketing management materials. Practitioner/Policy Implication: The results of this research can be used to help practitioner to develop and improve marketing strategies more effectively and efficiently, especially for coffee shop that target people in the city of Bandung as their consumers. Research Limitation/Implication: geography, number of sample, simple method